A Multi-scale Ecological Impact Assessment Method for Large-Scale Transmission and Transformation Projects: A Case Study of Zarut-Qingzhou ±800kV Direct Current Transmission Project - Mo, Hanqin; Liu, Shicun; Wen, Weibing; Liang, Dong; Chen, Xi; Zhao, Yanwei (Journal of Environmental Accounting and Management, 2026)
Ecological impact assessment (EcIA) of large-scale transmission and transformation projects has attracted attention, but assessment of the impacts of these projects is mostly conducted at a single scale and is not quantitative. Considering the potential impacts at different scales, an assessment index system is proposed to assess impacts at three different scales, namely at the scale of landscape, ecosystem, and sensitive areas. To express the multi-scale effect, the analytic hierarchy process (AHP) method was used to construct a hierarchical evaluation framework, and a comprehensive index was used to quantitatively evaluate the ecological impact. On this basis, a multi-scale EcIA method system for transmission and transformation projects was established. An assessment of impacts relating to the ZarutQingzhou ±800kV transmission project case study was conducted, and the results show that this multi-scale comprehensive EcIA method integrates the three scales well and can quantify the impacts both at the single scale and at multiple scales so that the evaluation is more objective and comprehensive. This study introduces a novel, accurate, and objective method for EcIA for large-scale transmission and transformation projects.